"Algae's sulfated polysaccharides modifications: Potential use of microbial enzymes". Issue 8 (August 2016) - Gurpilhares, Daniela de Borba; Moreira, Tatiane Rodrigues; Bueno, Julia da Luz; Cinelli, Leonardo Paes; Mazzola, Priscila Gava; Pessoa, Adalberto; Sette, Lara Durães
Graphical abstract: Highlights: Marine algae are valuable sources of structurally diverse bioactive compounds. Few studies focus on structural analysis and biological activities of sulfated polysaccharides. Microorganisms are potential producers of enzymes with biotechnological interests. Microbial enzymes could be used in sulfated polysaccharides modification. Abstract: Marine algae are valuable sources of structurally diverse bioactive compounds, among them, the group of sulfated polysaccharides (SPs). As an example of SPs, it could be cited the fucoidans in brown algae, carrageenans in red algae and ulvans in green algae. Since the past decades, SPs have been extracted from algae and evaluated in respect to their beneficial biological activities such as anti-inflammatory, antioxidative, antimicrobial, anticoagulant, antithrombotic, immunological and anticancer. This review deals with the presentation of natively bioactive SPs structural features in addition to already employed approaches of SPs structure modifications, such as chemical and physical methods. Moreover, this article presents the advantages and the importance of using enzymatic methods during SPs modification, and particularly, the use of microorganisms as enzymes sources. Enzymes such as hydrolases/glycosidases (e.g. fucoidanase, fucosidase, agarase and carrageenase), lyases, sulfotransferases and sulfatases could be used for this purpose. It has been shown that more studies are necessary to obtain/identify opportunities to create novel, or to intensify, SPs biological properties. Considering the advantages in the use of microbial enzymes in biotransformation processes, studies related to the modification of SPs by microorganisms should be stimulated.